Programa de educación financiera en directivos y docentes para mejorar la gestión responsable de los recursos económicos en la Institución Educativa Pública Teniente Manuel Clavero Muga Punchana 2022 - Petterman Macedo, Maija (2024)
The research presented aimed to evaluate the effect of a financial education program on responsible management of economic resources in directors and teachers of the Teniente Manuel Clavero Muga Public Educational Institution in the Punchana district in 2022. The results suggest that the educational program was effective in several dimensions related to economic resource management and understanding of the economic and financial system. The research design adopted was evaluative, field-based, univariate with a single group. The population and sample consisted of 58 participants among directors and teachers. An entry and exit test were applied, which was validated by experts. The study concludes that the averages of responsible management of economic resources before the application of the financial education program is lower (11.76) than the averages obtained after the application of the program (13.84), the standard deviations are very similar, which confirms that the financial education program was effective in improving responsible management of economic resources in directors and teachers of the educational institution.